Magang Bersertifikat di Kantor Akuntan Publik Basyiruddin dan Rekan - Handini Rahmadani; Syawwa Alfina Amelia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The increasing number of graduated students in universities has also resulted in high competition in job search. To overcome this problem, the Minister of Education and Culture, Nadiem Makarim made one of the new policies, namely Merdeka Belajar–Kampus Merdeka (MBKM). Universitas Islam "45" Bekasi collaborates with KAP Basyiruddin & Rekan as partners to carry out internship programs. The aims of the MBKM program are to prepare students to face the challenges of the world of work after graduating from college and to increase their value. The results of the internship at KAP Basyiruddin & Partners are that students can make bank confirmation letters and receipts, worksheets, bank reconciliations, input financial reports in ATLAS, complete letters and attach them to ATLAS, and make KKP audits. With this activity, students are expected to be able to go further than the competitors because they already have qualified experiences to immediately enter the business world.